Evaluasi Proses Bisnis Bagian Pemasaran dengan Metode Business Process Improvement (BPI) (Studi pada PT. Kencana Tiara Gemilang) - Dwi Ari Ambarsari Pratiwi; Yusi Tyroni Mursityo; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Kencana Tiara Gemilang is a plastic sheet manufacturing company that was founded in early 2014. Managed by professionals who have decades of experience in the plastics field. The author finds that there are several processes that are not carried out properly so that business processes become hampered or less effective. These indications are found in the marketing business process, namely the existence of activities that are still manual so that improvements will be made and there are activities that are not needed. This study uses the Business Process Model Natation (BPMN) diagram. From here, business processes are analyzed using the Failure Mode and Effect Analysis (FMEA) method and to make business process improvements using Business Process Improvement (BPI). Then the results of the current business process and the results of the recommendation business process are found in the marketing business process the average difference between the current business process and the recommendation is 37.25%, 49.18% in the business strategy plan sub-process and 74.27% on the sub business process marketing plan.